Developing a problem-based local history module to improve the critical thinking ability of senior high school students - Novita Mujiyati; Warto Warto; Leo Agung Sutimin (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2019)
This research aims at developing a problem-based local history module as learning media to improve the critical thinking ability of Senior High School students. This research employed a research and development (RD) method referring to ADDIE development design. The procedure of designing ADDIE development included (1) analyzing to identify the learning media needed, (2) designing to organize the material of module corresponding to basic competency and indicator, (3) developing to obtain the finished product of module through validation and limited and large-scale trials, (4) implementing the module during learning process, and (5) evaluating to find out the effectiveness of module. The results of the research show that the problem-based local history module effectively improves the students’ critical thinking ability. Through this module, the students are directed to understand a variety of aspects affecting a problem and relating it to the knowledge owned. The problems organized in the module are contemporary and related to the student environment. The process of connecting new knowledge to preexisting knowledge enables the students to develop their own knowledge and to improve their critical thinking ability in solving the problems.